Asymptomatic solitary cutaneous mastocytoma: A rare presentation - Dhruv Gopal; Poonam Puri; Avninder Singh; V Ramesh (Wolters Kluwer Medknow Publications, 2014)
A 50-day-old female child presented with asymptomatic skin colored raised lesion on the dorsal aspect of the left wrist since the age of 10 days. The diagnosis of cutaneous mastocytoma was made based upon clinical and histopathological features.